Analysis of the role of science and technology park in the economic development of the region (Case study: Pardis Park, Tehran) - Mohsen Saghaei; Ramin Amininejad; Said Ghasemizadeh (اقتصاد شهری)
The purpose of this research is to Analyze the role of a Science and Technology Park in the economic development of the studied area: Pardis Park of Tehran. This research was done using a descriptive-analytical method. The statistical population of this research includes all managers of companies that are members of Fardis Science and Technology Park, numbering 205 people. In this research, it was necessary to get information from people who were familiar with the subject. It is worth mentioning that according to the snowball method, 50% of the statistical population of 40 experts and managers was randomly surveyed so that the sample population was selected. The research tool for data collection was a questionnaire, which before implementation, its validity and reliability were confirmed. In this article, the effects and criteria affecting the economic development of the region as well as meaningful indicators are identified by regression method, and then by ANP method, the key success factors are prioritized, and then by TOPSIS method, strategy prioritization was carried out for the development of modern industries of Science and Technology Park. The results of the research showed that among the effects of the Science and Technology Park on economic development, there are factors such as introducing the future needs and necessities of the market, attracting more capital in the field of technology development, increasing investment in various economic sectors, and increase in employment and income level of companies in the region.